Treatment of Childhood and Adolescent Depression with Physical Rehabilitation - Olga Taranina (Journal of Global Pharma Technology, 2020)
One of the effective methods of treating depression in children and adolescents is exercising. The aim of the research is to study the effectiveness of physical activity in the treatment of psychogenic depression in children and adolescents. The sampling contained 90 children and adolescents (age 11-15 years) suffering from psychogenic depression, they were divided into 2 groups: group 1 (control group) – 45 children undergoing psychotherapy for 8 weeks; group 2 (study group) – 45 children who, in addition to psychotherapy, were treated with a complex of physical exercises 1 hour a day 4 times a week for 8 weeks. The main methods of the study were clinical-anamnestic and clinical-psychopathological methods, analysis of medical history and lifestyle data, anthropometry methods, laboratory and instrumental diagnostics, mathematical statistics methods. At the end of the 8th week of treatment, HAM-D score level of depression significantly decreased by 2.27 times (p